2011
DOI: 10.1177/104063871102300206
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Approaches to Estimate the Usefulness of Pooled Serum Samples for the Diagnosis of Postweaning Multisystemic Wasting Syndrome

Abstract: Abstract. Classical postweaning multisystemic wasting syndrome (PMWS) diagnosis is based on postmortem findings (histopathology plus viral detection in lymphoid tissues). Because one of the major differences between PMWS-affected and nonaffected pigs is Porcine circovirus-2 (PCV-2) load in serum and tissues, real-time quantitative polymerase chain reaction (qPCR) has been suggested as a potential diagnostic technique for the disease. The objective of the present study was to assess the applicability of qPCR to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…7 The majority of the reported pooling procedures have involved dichotomized test results demonstrating the presence or absence of a biological substance or organism. Quantitative investigations of pooled specimens have been evaluated for herd-level diagnosis of postweaning multisystemic wasting syndrome in pigs, 2 although pooling has primarily been used in relation to microarray experiments. Quantitative investigations using microarray technology have biological averaging as a basic assumption in relation to pooling.…”
Section: Introductionmentioning
confidence: 99%
“…7 The majority of the reported pooling procedures have involved dichotomized test results demonstrating the presence or absence of a biological substance or organism. Quantitative investigations of pooled specimens have been evaluated for herd-level diagnosis of postweaning multisystemic wasting syndrome in pigs, 2 although pooling has primarily been used in relation to microarray experiments. Quantitative investigations using microarray technology have biological averaging as a basic assumption in relation to pooling.…”
Section: Introductionmentioning
confidence: 99%
“…As with the higher proportion of positives, a higher viral load in oral fluid was expected because far more pigs were sampled with oral fluid. Earlier studies demonstrating a high variation of viral loads in serum between individual pigs within a group support this [ 18 , 44 ]: In 10 animals in each of 5 different PMWS-negative farms, ranges between <4 (detection limit) and 8.7 log(10) PCV2 copies per ml serum within the same farm and age group were found [ 18 ]. And in a vaccination trial, a mean level of 6.1 log(10) and a standard deviation of 1.7 log(10) PCV2 copies per ml serum in 8 PCV2-positive control pigs were reported [ 44 ].…”
Section: Discussionmentioning
confidence: 76%
“…Serum samples and nasal swabs have been suggested to be more suitable for evaluating PMWS status for a group of pigs than for individuals [ 9 ] and pooled samples could be a further development of this. However, it was later concluded that qPCR testing of pooled serum samples was not sufficiently reliable for diagnosis of PMWS at herd level but might be useful for determination of viral loads [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of pooling has been validated on field samples and shown to have limited effect on the sensitivity and specificity of the test (unpublished results), as has been shown by others [13]. The detection limit of the PCR assay used was 3 log 10 PCV2 copies/mL serum [12].…”
Section: Methodsmentioning
confidence: 94%